Some Factors Affecting Seed Viability of Leucaena leucocephala (Lmk. de Witt.) - Darma, I.G.K. Tapa (Jurnal Manajemen Hutan Tropika, 2003)
This study objective to determine (1) when appropriate harvesting peas, (2) methods of seed extraction by drying, (3) fungal pathogen attack young Leucaena leucocephala seed pods. Time proper harvesting is 62 days after flower buds. At this time reached the highest seed germination of 97.25%. Drying by blowing warm air without producing the lowest open pods compared with a gust of air drying with hot air blowing, the number of pods open: 20% of the pods No. 9; 21% of the pods No. 10; and 41% of the pod No .11 with the relative seed germination highest compared with other drying the second consecutive 87.13%, 44.25%, and 19.75%. However, the germination of seeds from the seed extraction method by blowing air without heating is still lower than the control. Pathogen fungus that attacks the seeds were Aspergillus sp. Alternaria sp., Pythium sp., and one unidentified species.